Efecto de Trichoderma harzianum para el control de Meloidogyne incognita, en el cultivo de tomate (Solanum lycopersicum L.) - Garcés Santana, Nidia Arely (2022)
: This bibliographic compilation details the effect of Trichoderma harzianum for the control of Meloidogyne incognita, in tomato crops (Solanum lycopersicum L.). The tomato is one of the most productive crops in the world and has a great nutritional value due to its nutritional qualities. Production can be affected by a variety of nematodes, of which M. incognita is the most prominent, due to its easy distribution, high frequency of infestation, because they produce alterations in the roots, causing galls, causing the injection of phytotoxic substances, the same ones that lead to the attack of pathogenic microorganisms, increasing the percentage of economic losses due to the decrease in yield and quality of the fruit. The dependence on nematicides can generate environmental and health problems for the consumer, due to the high prices of the products, farmers seek economic and sustainable alternatives for the management of M. incognita, with the use of Trichoderma harzianum that benefits the root of the plant making them more resistant to the attack of the nematode, it also has control mechanisms such as; competition for nutrients or space, antagonistic properties of antibiotics and mycoplasma that help control or eliminate pests